Autonomie der Trauer Zur Ambivalenz des sozialen Wandels - Benkel, Thorsten (Dimensionen der Sorge, 2019)
Funeral culture is changing rapidly. In recent years, graveyards and burial rituals in Germany have altered significantly. They no longer reflect mechanisms of collective sense-making; instead, they represent individual lifeworlds. Death and the decisions and actions surrounding it have, in effect, become characterised by pluralism.When it comes to legal regulations, however, no change is visible. The law does not interpret the aforementioned cultural transformation from the perspective of the bereaved. It is thus not surprising that graveyard rules and especially the stipulation that human remains may only be interred in a cemetery have come under criticism.Yet today, practices have evolved by which the bereaved can sidestep the rules and keep the ashes of their deceased relatives with them, or scatter them at alternative locations. The trigger for this silent revolution is individualisation. However much individual decisions play a role in this respect, this development is also the result of changes within the cultural mind. They both mark a shift towards mourning becoming more autonomous.